On Some Multidimensional Hilbert-Type Inequalities in the Discrete Case - Krnić, M.; Vuković, P. (Український математичний журнал, 2013)
Motivated by the results of Huang, we deduce a pair of discrete multidimensional Hilbert-type inequalities involving a homogeneous kernel of negative degree. We also establish conditions under which the constant factors involved in the established inequalities are the best possible. Finally, we consider some particular settings with homogeneous kernels and weight functions. In this way, we obtain generalizations of some results known from the literature. З метою узагальнення результат Хуанга отримано дві дискретні багатовимiрнi нєрівності гільбертового типу з однорідним ядром від'ємного степеня. Також встановлено умови, за яких сталі множники, що входять до отриманих нерівностей, є найкращими з можливих. Розглянуто деякі конкретні випадки однорідних ядер та вагових функцій. Це дає змогу узагальнити деякі відомі результати.